Accuracy of Fixed Implant‐Supported Dental Prostheses Additively Manufactured by Metal, Ceramic, or Polymer: A Systematic Review. (21st March 2022) - Rutkūnas, Vygandas; Gedrimienė, Agnė; Auškalnis, Liudas; Admakin, Oleg; Mangano, Francesco
Abstract: Purpose: Additive manufacturing (AM) in prosthodontics is used as an alternative to casting or milling. Various techniques and materials are available for the additive manufacturing of the fixed and removable tooth‐supported restorations, but there is a lack of evidence on the accuracy of AM fixed implant‐supported prostheses. Recent studies investigated the accuracy of ceramic AM prostheses. Therefore, the aim of this systematic review was to evaluate the accuracy of additively manufactured metal, ceramic or polymers, and screw‐ or cement‐retained fixed implant‐supported prostheses. Materials and Methods: Two calibrated investigators performed an electronic search of relevant publications in the English language following selected PICOS criteria and using a well‐defined search strategy (latest search date—1st of June, 2021). Based on the exclusion criteria (no control group, less than five samples per group, 3D printing of the implant abutment part, only subjective evaluation of accuracy, etc.) studies were not included in the review. Quantitative data of accuracy evaluation such as marginal gap, strain analysis, and linear measurements was extracted and interpreted. QUADAS‐2 tool was used to assess the risk of methodological bias of all included studies. Results: Sixteen in vitro studies were selected for the final analysis. Six of the selected studies evaluated screw‐retained restorations and 10 cement‐retained implant‐supported restorations. Only 4 publications concluded that AM restorations were more accurate than conventionally made (cast or milled) ones. The most common finding was that AM restorations were more accurate than cast and demonstrated less or similar accuracy compared to milled ones (n = 10 studies). Detected marginal discrepancies mean values of the AM prosthesis varied from 23 to more than 200 µm, but most of them were categorized as clinically acceptable. Conclusions: AM implant‐supported fixed prostheses demonstrate similar accuracy compared to conventional and computer‐aided design and computer‐aided manufacturing techniques in vitro. Detected inaccuracies of AM restorations do not exceed clinically acceptable limits. Clinical studies with longer follow‐up periods are needed to show the reliability of AM prostheses.